CONSUMER LOYALTY KARUNIA BARU SHIPPING COMPANY: SERVICE QUALITY, PRICE, AND CONSUMER SATISFACTION - Axel, Gilbert Anthoni (PERFORMA, 2022)
Abstract: This study aims to determine the effect of service quality, and perceived price fairness through consumer satisfaction on consumer loyalty at Karunia Baru Shipping Company. The sample in this study found 57 respondents who were determined by the saturation sampling technique and the data measurment tool used in this study is the Likert scale. The research method used is quantitative with the Partial Least Square-Structured Equation Model (PLS-SEM) technique using SmartPLS 3 software. The results of this study showed that, first, service quality had a significant positive effect on consumer satisfaction. Second, perceived price fairness had a significant positive effect on consumer satisfaction. Third, consumer satisfaction had a significant positive effect on consumer Loyalty. Fourth, service quality had a positive but not significant effect on consumer loyalty through consumer satisfaction. Fifth, perceived price fairness had a significant positive effect on consumer loyalty through consumer satisfaction. Based on these results it can be concluded that if Karunia Baru Shipping Company can provide a quality service and fair prices to their consumer, their consumers will be satisfied to the company. Even though the quality of service can make the consumer feel satisfied, it won’t make them loyal. However fair pricesfrom the company will make the consumer feel satisfied and eventually will be loyal to the company. Keywords: service quality, perceived price fairness, consumer satisfaction, consumer loyalty